2020
DOI: 10.56890/jpacd.v21i.3
|View full text |Cite
|
Sign up to set email alerts
|

Biology and chemistry of an Umbravirus like 2989 bp single stranded RNA as a possible causal agent for Opuntia stunting disease (engrosamiento de cladodios) - A Review

Abstract: Perhaps the most economically important disease of Opuntia ficus indica fruit cacti in Mexicois the “engrosamiento de cladodios” or macho disease. The symptoms of this disease, whichhas been suggested to be caused by a phytoplasma, are severe stunting of cladodes, flowersand fruits. In the mid-1980s this disease appeared in commercial cactus fruit orchards ofD’Arrigo Bros near Gonzalez, California. It was performed more than 30 PCR-based tests forviruses as well as various extraction methods and polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Similarly, it was expected that ULVs would require a helper virus to support infection as is observed for umbraviruses, which lack a CP and silencing suppressor. Curiously, several reports using next-generation sequencing did not identify a helper virus in plants infected with Group 2 ULVs, despite specific attempts to do so [ 40 , 44 , 60 ]. We have found that agroinfiltration of CY1 in N .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, it was expected that ULVs would require a helper virus to support infection as is observed for umbraviruses, which lack a CP and silencing suppressor. Curiously, several reports using next-generation sequencing did not identify a helper virus in plants infected with Group 2 ULVs, despite specific attempts to do so [ 40 , 44 , 60 ]. We have found that agroinfiltration of CY1 in N .…”
Section: Discussionmentioning
confidence: 99%
“…General time reversible model with gamma distribution rates and invariable frequency (GTR+G+I) was determined to be the best-fit substitution model in MEGA X and was implemented to construct the tree. The following ULV sequences were used: PMeV2 (KT921785), PpVQ (MT113180), BabVQ (MT113182) [ 42 , 93 , 94 ], OULV (MH579715, MT909563, MT909562) [ 44 ], FULV (MW480492, MW480492) [ 60 ], CY1 (JX101610) [ 40 ], CY2 (MT893741) [ 77 ], WULV (OK573479) [ 95 ], GULV(OP886321) [ 96 ], PIULV (OL330774) [ 97 ], SbaVa (MK211274) [ 98 ], TULV (OK018180) [ 99 ], MULV (OM937759) [ 41 ], JgULV (OM937760) [ 41 ], SULV (MN868593) [ 100 ], EMaV (MF415880), AgULV (OP660856), GPpTV1 (OM514399), ArULV (OQ102001) [ 101 ]. To analyze the phylogenetic relationship of ORF5 proteins with selected CPs and MPs, protein sequences were aligned using PROMALS3D [ 53 ] and trimmed in MEGA X.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is known that Luteoviridae provides the coat protein for trans-encapsidation of the Umbravirus RNA and allows its persistent transmission through an aphid vector [ 47 , 48 ], no helper virus has currently been associated with ulaRNAs. Indications that ulaRNAs must also possess a helper virus come from the finding of a Polerovirus-like virus along with OULV in aphids feeding on opuntia [ 49 ], even though evidence on actual transmissibility has never been provided. Thus, it can be hypothesized that, in cannabis as well as in other hosts, the occurrence of ulaRNAs dissociated from helper viruses comes from their loss after aphid transmission or during plant vegetative propagation.…”
Section: Categorizations Of Viruses and Viroid According To The Level...mentioning
confidence: 99%